154k views
2 votes
Solve the system by elimination
-2x+2y+3z=0, -2x-y+z=-3, 2x+3y+3z=5

User Ttyyll
by
6.3k points

2 Answers

4 votes

Answer:

Add the equations in order to solve for the first variable. Plug this value into the other equations in order to solve for the remaining variables.

Point Form:

(1,1,0)Equation Form:x =1 ,y =1 ,z =0

Explanation:

User Kay Van Bree
by
5.5k points
2 votes

The solution of -2x + 2y + 3z = 0, -2x - y + z = -3, 2x + 3y + 3z = 5 is x = 1 , y = 1 and z = 0.

Solution:

Need to solve given system of equation using elimination method.

-2x + 2y + 3z = 0 ------(1)

-2x - y + z = -3 ------(2)

2x + 3y + 3z = 5 ------(3)

As coefficients of x is same in (1) and (2) , subtracting (1) from (2) to eliminate variable x

(-2x - y + z) - (-2x + 2y +3z ) = (-3) - 0

=> -y + z – 2y – 3z = -3

=> -3y – 2z = -3

=> 3y + 2z = 3 --------(4)

On Adding equation 2 and 3 , we get our other equation in two variables y and z.

-2x - y + z + 2x + 3y + 3z = -3 + 5

=> 2y + 4z = 2

=> y + 2z= 1 ---------(5)

As coefficients of z is same in (4) and (5), subtracting (4) from (5) to eliminate variable z

(y + 2z) – (3y + 2z) = 1 – 3

=> -2y = -2

=> y = 1

Substituting y = 1 in equation 5, to get value of z

=> 1 + 2z = 1

=> 2z = 1 – 1 = 0

=> z = 0

Substituting y = 1 and z = 0 in equation (1) to get value of x

=> -2x + (2 x 1) + 3 x 0 = 0

=>-2x +2 = 0

=> -2x = -2

=> x = 1

Hence solution of given system is x = 1 , y = 1 and z = 0.

User Tomole
by
6.2k points